ChemInform Abstract: A Highly Active and Magnetically Recoverable Tris(triazolyl)—CuI Catalyst for Alkyne—Azide Cycloaddition Reactions. Issue 40 (30th September 2014) - Wang, Dong; Etienne, Laetitia; Echeverria, Maria; Moya, Sergio; Astruc, Didier
Abstract The tris(triazole) (MRC) is found to be a highly efficient catalyst for the title reaction.